Fast cell wall softening causes Venus flytrap closure - Jeongeun Ryu; Mathieu Colombani; Corentin Mollier; Joël Marthelot; Yoël Forterre (Science, 2026)
Plants can move rapidly without muscles, as seen in the Venus flytrap’s snapping lobes—a long-standing puzzle in plant biomechanics. Trap closure involves an elastic instability, but the active mechanical driver has remained elusive. Using in situ hydraulic and mechanical measurements, we identified the motor driving this transition. Closure occurs too quickly to be explained by water transport, revealing a distinct, nonhydraulic mechanism: a rapid (about one second) softening of the epidermal cell wall, releasing elastic energy stored in the trap. This represents the fastest modulation of wall mechanics reported in plants. Our finding reveals a mode of plant motility based on dynamic tuning of material properties, suggesting principles for muscle-free, bioinspired actuation.